Isla vs. continente. Un ensayo de historia conceptual - Lois, Carla (Revista de Geografía Norte Grande, 2021)
Throughout the history of modern geographical thought, some unexpectedly complex and intriguing debates arose surrounding the categories of island and continent. The origins of those arguments go back at least to the Renaissance, and they are still active even today. In this it is suggested that the island-continent relationship has been of four different types in geographical contexts: as part of a taxonomic system for landmasses; as a methodological analogy for considering both fieldwork and work in the laboratory for geographers; as two geographical elements that balance the whole and compose a harmonic unity; and as signs that imprint a particular character on human groups. This paper also proposes to recognize the resonances of each of those four types in the current modes of analyzing our geographies